THE SOLUBILITY OF d-VALINE IN WATER - Dalton, John B. (The Rockefeller University Press, 1936)
1. The solubility of d-valine in water has been determined over a range of 0–60°. 2. The solubility of this amino acid varies with the mode of crystallization, indicating a dependence of solubility on the crystal form.